2003
DOI: 10.1073/pnas.2435171100
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol enhances α 4 β 3 δ and α 6 β 3 δ γ-aminobutyric acid type A receptors at low concentrations known to affect humans

Abstract: ␥-Aminobutyric acid type A receptors (GABARs) have long been implicated in mediating ethanol (EtOH) actions, but so far most of the reported recombinant GABAR combinations have shown EtOH responses only at fairly high concentrations (>60 mM). We show that GABARs containing the ␦-subunit, which are highly sensitive to ␥-aminobutyric acid, slowly inactivating, and thought to be located outside of synapses, are enhanced by EtOH at concentrations that are reached with moderate, social EtOH consumption. Reproducibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
488
2
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 431 publications
(530 citation statements)
references
References 49 publications
36
488
2
4
Order By: Relevance
“…As noted earlier, low ethanol concentrations (3-30 mM) enhance the effects of GABA from transfected a 4 b X d and a 6 b X d GABA A receptor subunits expressed in vitro in oocytes (Sundstrom-Poromaa et al, 2002;Wallner et al, 2003). Consistent with ethanol having an effect on neurons with BZD-insensitive receptors, low concentrations of ethanol also selectively augmented the tonic GABA inhibition of granule cells that contain the a 4 and d GABA A receptor subunits, but did not have an effect on CA1 pyramidal cells containing the a 5 b 3 g 2/3 subunits (Wei et al, 2004).…”
Section: Proposed Role For Bzd-insensitive Gaba a Receptors In Ethanomentioning
confidence: 72%
See 4 more Smart Citations
“…As noted earlier, low ethanol concentrations (3-30 mM) enhance the effects of GABA from transfected a 4 b X d and a 6 b X d GABA A receptor subunits expressed in vitro in oocytes (Sundstrom-Poromaa et al, 2002;Wallner et al, 2003). Consistent with ethanol having an effect on neurons with BZD-insensitive receptors, low concentrations of ethanol also selectively augmented the tonic GABA inhibition of granule cells that contain the a 4 and d GABA A receptor subunits, but did not have an effect on CA1 pyramidal cells containing the a 5 b 3 g 2/3 subunits (Wei et al, 2004).…”
Section: Proposed Role For Bzd-insensitive Gaba a Receptors In Ethanomentioning
confidence: 72%
“…Roberto et al (2003) recently reported that 44 mM ethanol enhanced the effect of exogenously applied GABA to amygdaloid neurons, indicative that ethanol had a direct postsynaptic action on GABA A receptors at this site. Finally, the specific a 4 b X d and a 6 b X d GABA A receptor subunits (BZD-insensitive receptor subtypes), when expressed in oocytes, exhibited a direct action of low ethanol concentration enhancement of GABA responsiveness (Sundstrom-Poromaa et al, 2002;Wallner et al, 2003). More will be said later about this latter observation.…”
Section: In Vitro Examination Of Ethanol Action On Gaba a Receptor Fumentioning
confidence: 92%
See 3 more Smart Citations